Midwives' knowledge and use of partographs at Juba Teaching Hospital, South Sudan - Clara Roba Alfred; Siama Ladu Abdallah (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2017)
Background: Evidence shows that good knowledge of partographs and proper application of this knowledge results in a remarkable reduction in prolonged and obstructed labour and reduces maternal mortality. Obstructed labour can be prevented by a simple and cost-effective health intervention tool, the partograph. A partograph is a graphical record of the progress of labour and salient conditions of the mother and foetus plotted against time in hours. This provides an opportunity for early identification of deviation from normal progress. Early detection of prolonged labour greatly contributes to prevention of obstructed labour and related complications. Objective: To assess midwives' knowledge and use of partographs in the maternity ward of Juba Teaching Hospital, South Sudan. Methods: A cross-sectional descriptive study was conducted to assess utilisation of partographs among healthcare providers in Juba Teaching Hospital. All providers working at the time of the study were included. An interviewer administered questionnaire prepared in English was used to assess socio-demographic and other related variables of respondents as well as knowledge and practice. Ethical procedures were followed at every step. Results: Only 20% of the 30 respondents were registered midwives, 67% knew the components -of a partograph, and 93% could differentiate between normal and abnormal labour with the use of a partograph. The factors affecting the use of partographs included; shortage of partographs in the ward, lack of protocols on partograph use, understanding semantics of the English language, absence of refresher training, late reporting of mothers to the ward, and a shortage of staff. Conclusions: Despite good knowledge of the partograph, about half of the providers do not use them. We recommend training and recruitment of more qualified midwives, a continuous supply of partographs to improve use of partographs continuous supportive supervision, mentoring of staff and motivation schemes.